Method of obtaining of nonneuronal cultures of astrocytes, derivated from human mesenchymal stem cells - S. M. Gramatiuk; Yu. V. Іvanova; A. A. Hudyma (Клінічна хірургія)
Objective. Elaboration of method for obtaining of nonneuronal cultures of astrocytes, derivatives from human mesenchymal stem cells of various origin.